Aportes para una estrategia de protección al consumidor a adquirentes de viviendas - Urbano Jiménez, Elva Milagros (2024)
The present research examines the problems consumers face when purcha sing homes in Lima Metropolitan Area, including breaches by real estate companies. Key institutions such as Indecopi and the Ministry of Housing, Construction and Sanitation were consulted, and interviews were conducted with senior officials and private representatives. The proposed strategy includes the dissemination of preventive data on the housing market, the relaunch of the service 'Mira a quién le compras,' and the creation of an advisory commission to study the sector's issues and propose additional measures. The objective is to reduce the incidence of these problems.